Capability-promoting policies : enhancing individual and social development / edited by Hans-Uwe Otto, Melanie Walker and Holger Ziegler. - Otto, Hans-Uwe; Walker, Melanie; Ziegler, Holger (Policy Press, 2018)
This volume answers fundamental questions about how human development is fostered: How to overcome unjust societies with better distribution of opportunities to flourish? How can human development be revitalized in countries where social welfare is put into question?